Character Education In Cultural Sipakatau (Philosophy-Sociological Study In Bugis Communities) - Muhammad Tang; Abdul Rahim (International Journal on Advanced Science, Education, and Religion, 2019)
This paper will analyze, interpret and describe character education found in Sipakata culture or become the basis or basis in the development of character education. Character education in society is very important to be developed based on or based on local culture. The method used in this study is a qualitative type with field-based philosophical-sociological approach, with a Bugis community research locus in Barang village Soppeng district, South Sulawesi Province, Inodonesia. This study reveals that character education found in the Sipakatau Culture, including; mutual respect and respect, advise each other, love and love each other, support each other and protect, help / help each other, and have the same human rights before the Almighty God. These values ​​become the foundation in the development of character education which can be applied in society with three stages of planting, namely; the first stage; moral knowling (understanding the meaning contained in the cultural values ​​of Sipakatau), the second stage; moral feeling (feeling the benefits of these values), and the third stage, namely moral action; after feeling the benefits of this value there is encouragement or motivation to make behavior (action) in everyday life. So that these values ​​are embedded in the soul of the community.